The Emotions of Management and the Management of Emotions: A Case Study of Middle Managers in a Change Context - Moore, Caroline (Cranfield University, 2006)
The over-rational portrayal of middle managers has the intended or unintended consequence of masking and marginalising the emotional dimension demanded in this role. This research critically examines emotion at work, exploring how it is shaped and bound up with concepts such as control, power and fear. The framework used particularly focuses on both the emotions of control, and the control of emotions, which gives empirical support to the critique of over-rational views of management work. This research takes place longitudinally within an engineering company who have recently downsized by 50%, in a community which is tightly knit and lacks alternative employment opportunities. The overriding narrative of `site survival' is the key local discourse used, and this is explored through several discursive themes in evidence on site. This study explores how managerial emotion work involves the suppression and expression of emotion on a number of levels, as managers face off to multiple allegiances, some in direct tension with each other. This study illustrates how emotions are not merely the business of the individual, but are dynamic social constructions, and argues for an emotional framework that is relational rather than entitative. Emotions, their expression and suppression, are subject to, and situated within, numerous structural factors, and managers are subsequently both constrained and enabled by their environment. Far from being powerless, it is argued that managers are able to employ a number of resistant strategies and exert a degree of personal agency to alleviate tight emotion control. It is concluded that in times of change, emotion work represents a large but invisible part of the middle manager's role, yet is unacknowledged, unsupported and unscripted. By peeping beyond the `over-rational iron cage', this study provides rich empirical accounts which enhance our understanding of the emotion work carried out by middle managers.